Rehabilitation nursing of a patient with rotator cuff injury based on the ACTED framework (基于ACTED模式1例肩袖损伤患者的康复护理体会) - LIN Yanxiu (林彦秀); DING Yunxia (丁云霞); GU Chunping (古春平); HUANG Xiaoli (黄小丽) (中西医结合护理, 2025)
This study summarized the rehabilitation nursing of a patient with rotator cuff injury based on the ACTED framework. The ACTED framework (Assessment, Care, Treatment, Evaluation, Discharge) consisted of a detailed evaluation process, the formulation of multidisciplinary collaborative treatment, the implementation of individualized therapy, education for both patients and their family members, and mechanisms for continuous development and improvement. Nursing intervention based on the ACTED framework aimed to improve the recovery of shoulder function of the patient with rotator cuff injury, reduce pain and improve overall quality of life. (本文总结基于ACTED模式1例肩袖损伤患者的康复护理经验。ACTED康复护理模式涵盖了详细的评估流程、多学科协作治疗计划的制定、个性化的治疗方案实施、患者及其家属的教育, 以及持续的发展和改进机制, 通过跨学科合作改善肩袖损伤患者的肩关节功能障碍, 减轻疼痛, 加速康复进程, 并提升患者的整体生活质量。)